Room Temperature, Metal-Free, Regioselective Arylselenation of Anilines Using Diselenides as Selenium Source - Bai, Rekha; Dabaria, Kamlesh Kumar; Badsara, Satpal Singh (Synthesis, 2022)
A metal-free direct C–H selenation of aniline derivatives via an iodine-catalyzed C–Se bond formation using diselenides as a selenium source at ambient temperature is described. A variety of aniline derivatives underwent regioselective C–H selenation with different diselenides to afford the corresponding aryl selenoethers in good to excellent yields.
Keywords: C–H selenation; aniline derivatives; aryl selenoethers; regioselective; metal-free